Analisis Korelasi Disiplin Belajar dan Iklim Belajar dengan Prestasi Belajar Mata Pelajaran Keterampilan Ekstrakurikuler Pramuka Siswa SD Swasta Naungan Yayasan Buddhis di Kabupaten Tangerang - Puspita, Prita; Chandra, Alexander; Sutrisno, Sutrisno; Trikayani, Luluk; Gautama, Yohanes (ALACRITY : Journal of Education, 2022)
Problems in schools are many and quite complex, including a boring learning atmosphere for students, this causesobstacles in efforts to achieve good performance. In addition to efforts to get high academic scores, means for personality development are needed through various activities in the classroom, including extracurricular activities. To find out the problems in Buddhist Foundation Private Elementary Schools, data collection was carried out through questionnaires to elementary school teachers, parents of students with the results showing that the variables that most influenced learning achievement were learning discipline and learning climate. So, this research set the research title Quantitative Analysis of Correlation of Learning Discipline and Learning Climate on Student Achievement of Private Elementary Schools with Buddhist Foundations in Increasing Pramuka’s Extracurricular Skills in Tangerang Regency. The purpose of this study was to find out how the correlation of discipline and learning climate on learning achievement in extracurricular skills improvement. The population of this study were students of private elementaryschools who are auspices of Buddhist foundations in the city and district of Tangerang. The sample was taken based on the Yamane and Isaac and Michael sample formula, namely 133 samples. Inferential analysis is used to test the hypothesis using simple regression and correlation analysis techniques. The results showed that there was a simultaneous and partial influence between learning discipline and learning climate on the learning achievement of extracurricular skills subjects of private elementary school students under the auspices of the Buddhist Foundation in Tangerang Regency, with a coefficient of determination score X1 to Y of r2 = y1 0,218 with a correlation coefficient score generated by ry1 = 0,467 and the X2 to Y determination coefficient scoregenerated by r2 = 0,367 with a correlation coefficient score generated by r = 0,606 and the X1 to X2 determination y2 coefficient score generated by r2 = 0,377 with a correlation coefficient score generated by r = 0,614 the correlation y3 coefficient generated by r2 = 0,377, a contribution or influence of 37.7%, the remaining 62.3% is contributed by other y3 variables that have a relationship with increasing student achievement.